Absolutely, friend! 3 times 1 is simply 3. Just like painting a happy little tree, sometimes the simplest things can bring the most joy. Keep up the good work!
The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.The derivate of 3x is 3; the derivative of -1 is 0. So, the derivative of 3x-1 is simply 3.
You cannot add 3x and 1. You can add 3x and x and get 4x though.
-1/6 * 3x = -3x/6 = -x/2
3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3
12x2 + 7x + 1 = 12x2 + 3x + 4x + 1 = 3x*(4x + 1) + 1*(4x + 1) = (4x + 1)*(3x + 1)
No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²
So, we have 3x = 4 for some number x. We will solve for x. 3x = 4 (1/3)*(3x) = (1/3)*(4) [multiplied by (1/3) on both sides] x = 4/3
9x2 + 24xy + 16y2 = 9x2 + 12xy + 12xy + 16y2 = 3x(3x + 4y) + 4y(3x + 4y) = (3x + 4y)*(3x + 4y) = (3x + 4y)2
3x^5 If these are 5 of 3x multiplied together the it must be (3x)^5 =3^5 times x^5
1/3x + 6 = 9 Restating the problem x + 18 = 27 I multiplied by 3 x = 9 I subtracted 18 from 27
(3x - 3)(x/6)(x2 - x)= (3)(x - 1)(x/6)(x)(x - 1) = (1/2)(x2)(x -1)2 = (1/2)(x2)(x2 - 2x + 1) = (1/2)x4 - x3 + (1/2)x2
3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x
3x
It is: (3x-4)(3x+4) is the difference of two squares
9x2 + 6x + 1 = 9x2 + 3x + 3x + 1 = 3x(3x + 1) + 1(3x + 1) = (3x + 1)(3x + 1) or (3x +1)2
(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out
(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out